Improved Medication Adherence with the Use of Extended-Release Tacrolimus in Liver Transplant Recipients: A Pilot Randomized Controlled Trial - Manisha Verma; Radi Zaki; Johnathan Sadeh; John P. Knorr; Mark Gallagher; Afshin Parsikia; Victor Navarro (Journal of Transplantation)
Background. Nonadherence to immunosuppression in liver transplant recipients (LTRs) leads to deterioration in health outcomes. Once-dailyextended-release tacrolimus (TAC-ER) may improve adherence when compared to twice-dailyimmediate-release tacrolimus (TAC-IR). Methods. We conducted a randomized controlled study to evaluate medication adherence, clinical efficacy, and safety of TAC-ER in stable LTR. All patients >18 years who underwent liver transplantation before 6 months were eligible. Patients were randomized 1 : 1 to continued TAC-IR or conversion to TAC-ER. The primary outcome was change in medication adherence from baseline to 9 months, assessed using BAASIS. Secondary outcomes were tacrolimus trough levels, safety, and quality of life. Results. Thirty-one patients were consented and randomized to either of the two groups: conversion to TAC-ER (n = 15) or continued TAC-IR (n = 16). Six patients in the TAC-ER group withdrew after randomization due to apprehension about switching medication (n = 2), unwillingness to travel (n = 2), and increased liver tests after conversion (n = 2, both were acute rejections despite therapeutic tacrolimus levels and were considered unrelated to TAC-ER). We compared the results of nine patients in the TAC-ER group that completed the study with those of sixteen in the TAC-IR group. At baseline, there was no difference in tacrolimus trough levels between groups. Improved adherence was observed in the TAC-ER group as 100% of patients reported at least one period of full adherence during the study period (100% vs. 62.6%, p=0.035). Tacrolimus trough levels and liver tests were comparable between groups throughout the study. There were no differences in eGFR, HbA1c, or QoL between the groups. Conclusion. TAC-ER improved medication adherence while maintaining comparable trough levels, liver function, and QoL as TAC-IR in LTR.